Homoseksualitas: Tinjauan Kesehatan Reproduksi - Wahyuni, Budhy (Musawa Jurnal Studi Gender dan Islam, 2003)
The issue of homosexuality brings about various viewpoints that are controversial from any aspect. In terms of health, for example, many people link homosexuality as being the cause of the spread of HIV/AIDS, even though homosexuals themselves do not accept this accusation. In this article, Budi Wahyuni endeavours to look more "fairly" at this issue. According to her, HIV/AIDS and other sexually transmitted diseases are caused by unsafe sexual practices. Among those sexual acts vulnerable to the spread of sexually trans mitted diseases are oral sex, anal sex and masturbation, whether they are done by homosexuals or heterosexuals.